A high-stable and sensitive colorimetric nanofiber sensor based on PCL incorporating anthocyanins for shrimp freshness. (30th May 2022) - Liu, Li; Zhang, Junjun; Zou, Xiaobo; Arslan, Muhammad; Shi, Jiyong; Zhai, Xiaodong; Xiao, Jianbo; Wang, Xin; Huang, Xiaowei; Li, Zhihua; Li, Yanxiao
Highlights: PCL-based film immobilized with anthocyanins was prepared by electrospinning. PCL/PCL-CA bilayer film possessed excellent stability and sensitivity. Reversible color change of the film allows the repeated use for shrimp freshness evaluation. Colorimetric film indicated a warning by the remarkable color change at the early stage of spoilage. Abstract: A novel bilayer colorimetric film incorporating polycaprolactone (PCL) with clitoria ternatea Linn anthocyanin (CA) via electrospinning was designed. The PCL nanofibers layer acted as a protective layer against harsh environments as the strong hydrophobic with the WCA (water contact angle) values of 101.79°. The PCL-CA layer worked as an indicator for its significant color changes for pH. The sensitivity test verified the ammonia cycler reversibility of the nanofibers is promising for re-use packaging. And the PCL/PCL-CA film was characterized as suitable WVP (water vapour permeability), and the lower velocity of water penetrating. Moreover, higher elongation at break (240.431%), and color stability were achieved. Besides, the film exhibited the color change from pale-blue to yellow-green response as an indication of shrimp spoilage (21 h). These results suggested the potential application of the PCL/PCL-CA film for a reusable freshness sensor tool in food packaging.